Grid connected solar PV system using carbon material based DYE sensitized solar cells. (2021) - Varshney, Gunjan; Chauhan, D.S.; Dave, M.P.
Abstract: In recent time, third generation solar cells have been developed and become very popular as DYE sensitized solar cells (DSSC). These carbons based DSSC are eco-friendly, having less carbon credit and low in manufacturing cost as compare to second generation thin film solar cells. Overall performance of grid connected PV based electrical systems are affected by the selection of the solar cells and modules. In this work, carbon-based DYE sensitized solar cells have been used for the grid connected PV systems. Here, performance of DSSC based grid connected system is presented in result section. DC link voltage and bidirectional power flow have been shown here to validate the performance of grid connected solar PV system. Simulation work has been done on MATLAB software and different results have been shown in graphical form.